The Effect of a Novel Form of Biotin, JDS-MB-001, on Remyelination in a Hippocampal Demyelination Animal Model - Komorowski, James; Ojalvo, Sara Perez; Sylla, Sarah; Orhan, Cemal; Tuzcu, Mehmet; Ozercan, Ibrahim H.; Şahin, Kazım (Sage Publications Ltd, 2019)
[Abstract Not Available]
Americas-Committee-for-Treatment-and-Research-in-Multiple-Sclerosis (ACTRIMS) Forum -- FEB 28-MAR 02, 2019 -- Dallas, TX